The ALMA view of UV-irradiated cloud edges: unexpected structures and processes. Issue Volume 13:Issue S332(2017) (4th September 2018) - Goicoechea, Javier R.; Cuadrado, S.; Pety, J.; Aguado, A.; Black, J. H.; Bron, E.; Cernicharo, J.; Chapillon, E.; Fuente, A.; Gerin, M.; Joblin, C.; Roncero, O.; et al.
Abstract: Far-UV photons (FUV, E < 13.6 eV) from hot massive stars regulate, or at least influence, the heating, ionization, and chemistry of most of the neutral interstellar medium (H i and H2 clouds). Investigating the interaction between FUV radiation and interstellar matter (molecules, atoms and grains) thus plays an important role in astrochemistry. The Orion Bar, an interface region between the Orion A molecular cloud and the H ii region around the Trapezium cluster, is a textbook example of a strongly illuminated dense PDR (photodissociation region). The Bar is illuminated by a FUV field of a few 10 4 times the mean interstellar radiation field. Because of its proximity and nearly edge-on orientation, it provides a very good template to investigate the chemical content, structure, and dynamics of a strongly irradiated molecular cloud edge. We have used ALMA to mosaic a small field of the Bar where the critical transition from atomic to molecular gas takes place. These observations provide an unprecedented sharp view of this transition layer (≲ 1″ resolution or ≲ 414 AU). The resulting images (so far in the rotational emission of CO, HCO +, H 13 CO +, SO +, SO, and reactive ions SH + and HOC + ) show the small-scale structure in gas density and temperature, and the steep abundance gradients. The images reveal a pattern of high-density substructures, photo-ablative gas flows and instabilities at the edge of the molecular cloud. These first ALMA images thus show a more complex morphology than the classical clump/interclump static model of a PDR. In order to quantify the chemical content in strongly FUV-irradiated gas, we have also used the IRAM-30 m telescope to carry out a complete line-survey of the illuminated edge of the Bar in the millimeter domain. Our observations reveal the presence of complex organic molecules (and precursors) that were not expected in such a harsh environment. In particular, we have reported the first detection of the unstable cis conformer of formic acid (HCOOH) in the ISM. The energy barrier to internal rotation (the conversion from trans to cis ) is approximately 4827 cm −1 (≈7000 K). Hence, this detection is surprising. The low inferred trans -to- cis abundance ratio of 2.8±1.0 supports a photoswitching mechanism: a given conformer absorbs a FUV stellar photon that radiatively excites the molecule to electronic states above the interconversion barrier. Subsequent fluorescent decay leaves the molecule in a different conformer form. This mechanism, which we have specifically studied with ab initio quantum calculations, was not considered so far in astrochemistry although it can affect the structure of a variety of molecules in PDRs.